The Role of the Family in the Prevention and Control of Stunting During the Covid-19 Pandemic In Kauman Village RT 16 RW 08 Wiradesa Subdistrict, Pekalongan Regency - Ardiana Priharwanti; Riska Amalia (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
Pekalongan district was ranked 4th in Central Java as district with nutritional problems that have not been handled optimally. The result of weighing 10.316 children under five carried out in 2020 showed that 1.631 children under five were indicated stunting. Intervention activities in reducing stunting problem are carried out by team through 2 methods (offline and online) within a month from November 23 until December 23, 2021 in Kauman village. The offline method is carried out by “door to door” to avoid crowds and Focus Group Discussion (FGD) while still adhering to health protocols. Online activities are carried out through WhatsApp groups, Google Meet, and Youtube. Intervention activities has been done by 5 activities: 1) 3P+S: Placing Clean & Healthy Lifestyle and Stunting Posters, 2) 'EDULINTING' Stunting Mobile Education, 3) Movement for Parents to Understand Nutrition, Stunting Free Children, 4) CEMANGGI (Healthy and Nutritious Snack): Pumpkin Flavored Milk Pudding, and 5) FGD: DWM 'Discuss With Mom' with PARENTING theme. As a result of this activity, there has been a change in the behavior of the local community to become healthier in terms of eating patterns and increasing a clean and healthy lifestyle.